2008
DOI: 10.1074/jbc.m800315200
|View full text |Cite
|
Sign up to set email alerts
|

SoxAX Cytochromes, a New Type of Heme Copper Protein Involved in Bacterial Energy Generation from Sulfur Compounds

Abstract: SoxAX cytochromes are essential for the function of the only confirmed pathway for bacterial thiosulfate oxidation, the socalled "Sox pathway," in which they catalyze the initial formation of a S-S bond between thiosulfate and the SoxYZ carrier protein. Our work using the Starkeya novella diheme SoxAX protein reveals for the first time that in addition to two active site heme groups, SoxAX contains a mononuclear Cu II center with a distorted tetragonal geometry and three to four nitrogen ligands, one of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…Kappler et al (36) have proposed an essential role for Cu(II) in SoxAX catalysis. The work presented here corroborates previous studies in finding no indication of a site for binding Cu(II) within the structure of the enzyme resolved by x-ray crystallography (36). Thus, we propose that the activity of SoxAX originates from its heme cofactors and/or their ligands.…”
Section: Discussionsupporting
confidence: 80%
“…Kappler et al (36) have proposed an essential role for Cu(II) in SoxAX catalysis. The work presented here corroborates previous studies in finding no indication of a site for binding Cu(II) within the structure of the enzyme resolved by x-ray crystallography (36). Thus, we propose that the activity of SoxAX originates from its heme cofactors and/or their ligands.…”
Section: Discussionsupporting
confidence: 80%
“…thiosulfatophilum [44]) or triheme type (P. pantotrophus [49] and R. sulfidophilum [3]) were reported to be in the range of about ϩ135 to 200 mV. More recently, it was reported that one of the hemes has an unusually low midpoint redox potential of Ϫ432 mV in the triheme SoxAX complex from P. pantotrophus (49) and Ϫ479 mV in the diheme protein from Starkeya novella (33), respectively. Our results show that one of the hemes in the diheme SoxAX-SAXB complex from C. tepidum has a very low redox potential and that rSoxA contains this low-potential heme (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The midpoint redox potential at pH 10.0 of rSoxX was ϩ135 mV, but that of rSoxA was unusually low, with a value of less than Ϫ550 mV. Previously, the midpoint redox potentials of all the hemes of SoxAX, irrespective of whether they were the diheme type (S. novella [33] and C. limicola f. sp. thiosulfatophilum [44]) or triheme type (P. pantotrophus [49] and R. sulfidophilum [3]) were reported to be in the range of about ϩ135 to 200 mV.…”
Section: Discussionmentioning
confidence: 99%
“…Axial heme-thiolate ligation of a c-type heme group is unusual, and it has been noted that the His/Cys ligation of the SoxA hemes (6 -8, 10) gives rise to a number of unusual features, including an extremely low redox potential below Ϫ400 mV (11,12) and a modification of the ligand to a cysteine persulfide that was shown to exist in the group 1 SoxAX proteins (8,9,13). It has been suggested that this modification is responsible for the multiple EPR active states observed for the SoxA active site heme (7,(12)(13)(14).…”
mentioning
confidence: 99%